Predicted Impact of COVID-19 on Neglected Tropical Disease Programs and the Opportunity for Innovation. (28th September 2020) - Toor, Jaspreet; Adams, Emily R; Aliee, Maryam; Amoah, Benjamin; Anderson, Roy M; Ayabina, Diepreye; Bailey, Robin; Basáñez, Maria-Gloria; Blok, David J; Blumberg, Seth; Borlase, Anna; Rivera, Rocio Caja; et al.
Abstract: Due to the COVID-19 pandemic, many key neglected tropical disease (NTD) activities have been postponed. This hindrance comes at a time when the NTDs are progressing towards their ambitious goals for 2030. Mathematical modelling on several NTDs, namely gambiense sleeping sickness, lymphatic filariasis, onchocerciasis, schistosomiasis, soil-transmitted helminthiases (STH), trachoma, and visceral leishmaniasis, shows that the impact of this disruption will vary across the diseases. Programs face a risk of resurgence, which will be fastest in high-transmission areas. Furthermore, of the mass drug administration diseases, schistosomiasis, STH, and trachoma are likely to encounter faster resurgence. The case-finding diseases (gambiense sleeping sickness and visceral leishmaniasis) are likely to have fewer cases being detected but may face an increasing underlying rate of new infections. However, once programs are able to resume, there are ways to mitigate the impact and accelerate progress towards the 2030 goals. Abstract : The COVID-19 pandemic has disrupted neglected tropical disease programs. Modelling shows the impact of this will vary across diseases. Once interventions are reintroduced, there are opportunities for mitigating the delay and accelerating progress towards the 2030 goals.